Rancangan Alat Bantu Proses Sablon Kaos dengan Pendekatan Ergonomi di Laboratorium Teknik Industri Universitas Pamulang - Jawad, Aod Abdul; Ibu, Deajeng Setia (Jurnal Optimalisasi, 2025)
In a company there are several machines and each machine has specifications that can be used for the process of making products where each machine has advantages and disadvantages. The aim of this research is to find out how to design tools that suit the needs of t-shirt screen printing operators using an anthropometric approach  and to find out whether the design of these tools can help operators be safer and more comfortable when carrying out the t-shirt screen printing process in the Industrial Engineering Laboratory and this research was carried out in a comprehensive manner. observational using the anthropometric measurement method and using the Nordic Body Map recapitulation by taking 3 operator samples for the anthropometric measurement method and distributing questionnaires to 12 operators. Then the results are processed and the highest score is obtained, namely at the pressing work station with an individual score (50-70) with a moderate risk level, improvements may be needed. The anthropometric measurement method was carried out by measuring 3 samples of t-shirt printing operators, then calculating the average, standard deviation and percentile calculation using the 50th percentile and the final results were obtained for the design size of the table aid with height: 85, width: 70 and length: 151